POSITIVE AND NEGATIVE FACTORS OF THE INVESTMENT CLIMATE IN UKRAINE - Fedorchak O.V. (Pressing Problems of Public Administration, 2016)
The article considers the essence of the positive and negative factors of investment climate in Ukraine. We described the dynamics international indexes of “doing business” and “economic freedom” and their components. The positive and negative factors of investment climate in Ukraine are determined.